2021
DOI: 10.1002/ijc.33704
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node metastases in breast cancer: Investigating associations with tumor characteristics, molecular subtypes and polygenic risk score using a continuous growth model

Abstract: We investigate the association between rate of breast cancer lymph node spread and grade, estrogen receptor (ER) status, progesteron receptor status, decision tree derived PAM50 molecular subtype and a polygenic risk score (PRS), using data on 10 950 women included from two different data sources. Lymph node spread was analyzed using a novel continuous tumor progression model that adjusts for tumor volume in a biologically motivated way and that incorporates covariates of interest. Grades 2 and 3 tumors, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…Cardozo et al 25 and Li et al 26 found that interval cancers were associated with lower PRS. Our results show agreement with Ishden et al 24 and Cardozo et al 25 because our results show little difference in the sojourn time between low risk and high risk based on PRS. Lower-risk cancers had shorter sojourn time than higher-risk cancers, although this difference was not significant.…”
Section: Misclassificationsupporting
confidence: 93%
See 1 more Smart Citation
“…Cardozo et al 25 and Li et al 26 found that interval cancers were associated with lower PRS. Our results show agreement with Ishden et al 24 and Cardozo et al 25 because our results show little difference in the sojourn time between low risk and high risk based on PRS. Lower-risk cancers had shorter sojourn time than higher-risk cancers, although this difference was not significant.…”
Section: Misclassificationsupporting
confidence: 93%
“…However, the finding that sojourn time does not vary substantially by risk group, that is, higher risk is not associated with faster progression or more aggressive disease, is aligned with other studies. Taghipour et al 23 Isheden et al 24 found no association between the rate of lymph node spread, a measure of tumor aggressiveness, and PRS. Cardozo et al 25 and Li et al 26 found that interval cancers were associated with lower PRS.…”
Section: Misclassificationmentioning
confidence: 99%
“…The data on distant metastases has been used before to study the association of mammographic density and the risk of distant spread 22 ; the (marginal) natural history model of lymph node spread was also developed using CAHRES (and other) data. 14 , 23 , 24 Mammographic images and screening histories were collected from mammography screening units and radiology departments, in an extension of the original case-control study; the collection of this data has also been described previously. 25 , 26 CAHRES is an old study, which for us has several advantages: first, there is an adequate follow-up to study breast cancer spread to distant metastasis.…”
Section: An Analysis Of Data From Swedish Postmenopausal Breast Cance...mentioning
confidence: 99%
“…A vast number of molecular subtypes of BC exist with Luminal B-like human epidermal growth factor receptor 2 negative (Luminal B [HER2−]), which accounts for more than half the cases of BC, 5 has a longer recurrence-free and metastasis-free survival rate. 6 Owing to the heterogeneity in their clinical behavior, 7 , 8 development of a special population occurs as patients evolve from BC to LM; thus, special clinicopathological characteristics can be seen within this special internal environment. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…A vast number of molecular subtypes of BC exist with Luminal B-like human epidermal growth factor receptor 2 negative (Luminal B [HER2−]), which accounts for more than half the cases of BC, 5 has a longer recurrence-free and metastasis-free survival rate. 6 Owing to the heterogeneity in their clinical behavior, 7,8 development of a special population occurs as patients evolve from BC to LM; thus, special clinicopathological characteristics can be seen within this special internal environment. 9,10 The clinical features of the relationship between BC and LM are poorly defined; thus, defining the high-risk clinicopathological characteristics for individuals and determining the possible treatment options may provide a reference for the inclusion criteria of new clinical trials directed toward patients with high risk of LM.…”
Section: Introductionmentioning
confidence: 99%